Exploring urban–rural inequities in older adults life expectancy: a case study in Zhejiang, China for health equity - Chen, Yongguo; Fan, Xiaoting; Shen, Shusheng; Chen, Yong; Pan, Zhiwei; Chen, Zixuan; Zhong, Haoqiang; Li, Menglong (Frontiers in Public Health, 2025)
This study investigates the inequities in life expectancy among individuals aged 65 and above in urban and rural areas of Zhejiang Province, China, with a primary focus on promoting health equity among the older adults population. The objective is to analyze the trends and factors contributing to the urban–rural gap in life expectancy and to propose strategies for reducing this disparity. Data from the 2010 and 2020 statistical records and census data were analyzed using cohort life tables and gray correlation analysis. Results indicate an overall increase in life expectancy among the older adults, with a more pronounced improvement in rural areas, thereby narrowing the urban–rural gap from 1.53 years in 2010 to 1 year in 2020. Income inequality emerges as the primary factor influencing life expectancy, followed by educational attainment, with variations across different age groups and gender. This underscores the importance of tailored interventions that consider the specific needs of older adults individuals in diverse geographical areas and age brackets to extend life expectancy and promote health equity. By tackling these unfair differences, health equity can be ensured and the overall well-being of the older population in both urban and rural areas can be improved.